2006
DOI: 10.1381/096089206776116372
|View full text |Cite
|
Sign up to set email alerts
|

Central Mechanisms of Gastric Electrical Stimulation Involving Neurons in the Paraventricular Nucleus of the Hypothalamus in Rats

Abstract: GES activates gastric-related neurons in the PVN, and the excitatory effect of GES seems related to stimulation strength. The GES used for treating gastroparesis and the GES used for treating obesity seem to solicit different neuronal responses in the PVN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 32 publications
5
29
0
Order By: Relevance
“…These results suggested that both the frequency and width of the stimulation pulse play an important role in the modulation of thoracic spinal neuronal activity. In general, results are similar to observations on the effects of GES on neuronal activity in the nucleus of the solitary tract and in the paraventricular nucleus of hypothalamus in rats (Qin et al 2005;Tang et al 2006). …”
Section: Effects Of Gessupporting
confidence: 88%
See 1 more Smart Citation
“…These results suggested that both the frequency and width of the stimulation pulse play an important role in the modulation of thoracic spinal neuronal activity. In general, results are similar to observations on the effects of GES on neuronal activity in the nucleus of the solitary tract and in the paraventricular nucleus of hypothalamus in rats (Qin et al 2005;Tang et al 2006). …”
Section: Effects Of Gessupporting
confidence: 88%
“…In the present study, we used four sets of stimulation parameters and the selection of these parameters was based on the following: Parameter A is the set of parameters commonly used for the treatment of obesity (D'Argent et al 2002); in parameter B, the frequency is reduced to 14 Hz which is commonly used in treating nausea and vomiting in patients with gastroparesis (Abell et al and Forster et al 2002); Parameter C is similar to Parameter A except that the pulse width is increased to 3ms. The reason behind this selection is that this set of parameters was known more effective in activating GD-responsive neurons in the paraventricular nucleus (Tang et al 2006). Parameter D is typically used to alter gastric motility functions (Ouyang et al 2005).…”
Section: Effects Of Gesmentioning
confidence: 99%
“…These results suggested that both the frequency and width of the stimulation pulse play an important role in the modulation of thoracic spinal neuronal activity. In general, these data are similar to previous observations on the effects of GES on the activity of thoracic spinal neurons with gastric input (Qin et al 2007), and on neuronal activity in the nucleus of the solitary tract and in the paraventricular nucleus of the hypothalamus in rats (Qin et al 2005;Tang et al 2006). Because a large overlap of spinal innervation for the stomach and duodenum occurs in the lower thoracic segments (Hazarika et al 1964;Khurana and Petras 1991), it is likely that spinal afferent impulses evoked by GES activated spinal neurons that also received primary input from the duodenum.…”
Section: Effects Of Gessupporting
confidence: 91%
“…60 All three methods of GES (short pulse, long pulse and trains of short pulses) were able to activate these neurones. However, in one specific type of neurones (gastric distention-inhibitory neurones), opposite effects were noted between GES with trains of short pulses (with parameters used for treating obesity) and GES of short pulses (with parameters used for treating nausea and vomiting in patients with gastroparesis).…”
Section: Central Neuronal Effectsmentioning
confidence: 91%